Numerical investigation on the scale-up rules of a supercritical water fluidized bed reactor using the two-fluid model - Hao Zhang (Taylor & Francis Group, 2021)
The supercritical water fluidized bed reactor (SCWFBR) is a novel hydrogen production technique, so the understanding on its scale-up is limited. In this regard, the trial-and-error procedure is not an option for traditional experimental research because it is costly and high risk. To overcome these problems, numerical simulations were carried out in this study based on the two-fluid model (TFM) to examine the capability of different scale-up rules for the SCWFBR. The numerical model was first validated based on experimental results. Then, four different-sized SCWFBRs were designed, in which numerical simulations for both air–solid and supercritical water (SCW)–solid systems were conducted following different scale-up rules. The distributions of solid volume fraction, solid velocity and pressure in these reactors were fully investigated. Comparisons among the numerical results showed that keeping the Reynolds number, Froude number and dimensional inlet velocity constant is critical for the scale-up of both SCWFBRs and traditional gas–solid fluidized bed reactors (FBRs). Moreover, keeping the particle diameter constant is helpful in obtaining the similarity of the multiphase flow behavior. For the SCWFBR, but not for the traditional gas–solid FBR, a constant density ratio between solid and fluid should be kept during the scale-up. Finally, for the SCW–solid system with more active particle motions, the effect of the interparticle collisions should be considered in the scaling parameters at high Reynolds numbers.